Ekonomiczne aspekty obowiązku wykorzystania energii ze źródeł odnawialnych - Graczyk, Andrzej (Economic Aspects of the Obligatory Use of Renewable Energy Resources, 2007)
Many regulations have been introduced to Polish law as a result of the EU Directive 2001/77/EC on the promotion of the electricity produced from renewable energy source in the internal electricity market. These changes are discussed in this article and the solutions applied are analyzed using the criterion of maximization of net social benefits. Based on this analysis, it can be argued that when the costs of renewable energy are not similar to the costs of conventional energy, it is not certain whether a change from conventional to renewable energy is socially beneficial. Furthermore, it is necessary to take into consideration the external costs of both types of energy. The introduction of renewable energy does not guarantee the elimination of emissions from the production of conventional energy causing the highest external costs. It may even be possible that renewable energy will replace the production of conventional energy with the lowest level of emission and external costs per unit.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (14); 2007; nr 1164, s. 118-125